2011
DOI: 10.1387/ijdb.113359jt
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation regulates galectin-3/ligand interplay during mammary tumour progression - a case of targeted uncloaking

Abstract: Galectin-3 is involved both in facilitating detachment of cells from primary tumour sites and favouring cancer cell adhesion and survival to anoikis in the blood stream. The mechanisms behind these apparently contradictory roles of the lectin have not yet been resolved. In order to investigate possible interplays between galectin-3 and its ligands underlying their role in the metastatic process, we examined mucin-1 (MUC1) and epidermal growth factor receptor (EGFR), well-known galectin-3 ligands, as well as ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…In line with our observations, much of the literature showed that ST6GAL1 promotes cell migration and invasion during cancer progression (28,29). The function of ST6GAL1 in promoting cell migration might be partially mediated through affecting galectin-involved signalings because galectin-3 is highly correlated with cancer malignancy by regulating various biological processes (30,31), and ␣2,6-sialylation of ␤1 integrin could impair their interaction with galectin-3, thereby facilitating cell migration (32). On the other hand, accumulating evidence suggested that ST6GAL1 renders the cells resistant to apoptosis.…”
Section: Discussionsupporting
confidence: 86%
“…In line with our observations, much of the literature showed that ST6GAL1 promotes cell migration and invasion during cancer progression (28,29). The function of ST6GAL1 in promoting cell migration might be partially mediated through affecting galectin-involved signalings because galectin-3 is highly correlated with cancer malignancy by regulating various biological processes (30,31), and ␣2,6-sialylation of ␤1 integrin could impair their interaction with galectin-3, thereby facilitating cell migration (32). On the other hand, accumulating evidence suggested that ST6GAL1 renders the cells resistant to apoptosis.…”
Section: Discussionsupporting
confidence: 86%
“…Sialylation was reported to regulate interaction between galectin-3 and ligand in tumor cells and the mechanisms are crucial in regulating adhesive and de-adhesive events in the invasive capacity of metastatic cells (26). We hypothesized that the masking effect of ligand by sialylation may be important in cell adhesion and invasion to galectins which are known to deposit in the tumor environment.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the activation of Slug and Snail transcription factors and the as opposed to uniform cell membrane expression, further suggesting a role for MUC1 and EGFR in cell motility. 86 Recently, our laboratory published evidence that MUC1 and EGFR regulate the expression of c-Met, the hepatocyte growth factor/scatter factor receptor. c-Met is a receptor tyrosine kinase that is often upregulated in metastatic cancers and is involved in metastatic progression (reviewed in Peschard).…”
mentioning
confidence: 99%